2020
DOI: 10.1093/clinchem/hvz015
|View full text |Cite
|
Sign up to set email alerts
|

The Silence Speaks, but We Do Not Listen: Synonymous c.1824C>T Gene Variant in the Last Exon of the Prothrombin Gene as a New Prothrombotic Risk Factor

Abstract: Background Thrombosis is a major global disease burden with almost 60% of cases related to underlying heredity and most cases still idiopathic. Synonymous single nucleotide polymorphisms (sSNPs) are considered silent and phenotypically neutral. Our previous study revealed a novel synonymous FII c.1824C>T variant as a potential risk factor for pregnancy loss, but it has not yet been associated with thrombotic diseases. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 142 publications
(159 reference statements)
1
12
0
Order By: Relevance
“…Thrombophilia testing showed that patient was homozygous carrier for PAI-1 4G/5G and MTHFR C677T mutations. Additional analysis revealed the presence of recently reported FII c.1824C>T gene variant in heterozygous state (10) and elevated plasma prothrombin level.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Thrombophilia testing showed that patient was homozygous carrier for PAI-1 4G/5G and MTHFR C677T mutations. Additional analysis revealed the presence of recently reported FII c.1824C>T gene variant in heterozygous state (10) and elevated plasma prothrombin level.…”
Section: Discussionmentioning
confidence: 75%
“…Taking into account that thrombophilia testing showed our patient is not a carrier of this variant, we decided to look into novel potential variants in FII gene associated with early IS onset and did sequencing of 715 bp within its 3` end, where a recently described FII c.1824C>T gene variant was detected. The FII c.1824C>T represents a synonymous FII variant leading to the CGC to CGT codon replacement, on the Arg608 position in the protein (10). The study by Pruner et al showed increased frequency of c.1824C>T gene variant in patients who suffered IS compared to healthy controls (4.8% vs. 0.9%), and 5.4-fold greater risk for IS occurrence in variant carriers (10), in vitro examination demonstrated that FII c.1824T allele is associated with elevated expression of prothrombin mRNA (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations